POLEMIK CALON INDEPENDEN PADA PEMILUKADA ACEH 2012 DALAM FRAMING MEDIA LOKAL - Fadhillah Sri Meutia; Firdaus Mirza Nusuary (Fakultas Dakwah dan Komunikasi, 2016)
This research focuses on the politics of the local media in Aceh Election 2012 through framing analysis to see how the trend towards political media (of) Serambi Indonesia and (Aceh’s) Modus Aceh of constructing and framing polemic (I)independent candidates who make an impact on Aceh election 2012. It is worth noting that on a mass media, economic factors into an external force that affect the appearance of media content, i.e. investors, audiences and advertisers. While internal factors, influenced by the figure of journalists who have attitudes, values, beliefs and a particular orientation in ideology, politics, religion, and ethnicity, that influence in constructing reality. (To consider) see geopolitical conditions in Aceh, the local media (does not) did not fully have greater freedom in constructing reality influenced by (ideological, political and economical interest) ideological interests, politically and economically. Polemics related to (I)independent candidates, researchers found (out that there is) difference between the two media reports (construct differently and provide a positive image in every single of their reports) that in any preaching, doing construction differently and provide a positive image. (Regarding to the news of rejection of Independent candidates brings about a bit impact on politics in Aceh even in national region, so as to give a policy to postpone the election) News regarding the rejection of independent candidates in the news The constructed more or less warming impact on politics in Aceh, up to the national level so as to give a policy to postpone the election.